Enhanced visible-light-driven photocatalytic degradation of azo dyes by heteroatom-doped nickel tungstate nanoparticles - Alharthi Fahad A.; Albaeejan Mohammed Abdullah; Alshayiqi Alanoud Abdullah; Aldubeikl Hend Khalid; Hasan Imran (Nanotechnology Reviews, 2023)
In this study, we conducted the hydrothermal synthesis of cobalt (Co)–doped NiWO4, resulting in the formation of Co–NiWO4 nanoparticles (NPs), followed by calcination at 550℃ for 12 h. Comprehensive analyses were performed to characterize the composition, structure, and morphology of the synthesized material. X-ray diffraction results confirmed the successful inclusion of Co in the NiWO4 lattice, with the presence of characteristic peaks of CoWO4. The crystallite size, determined using the Scherrer equation, was measured to be 22 nm. Using UV-Vis spectroscopy and Tauc’s equation, we calculated the band gap energy (E g) to be 3.75 eV for NiWO4 and 1.75 eV for Co–NiWO4. The potential application of the synthesized material as a photocatalyst was investigated for the degradation of the diazo dye Congo red (CR). Under optimized reaction conditions, Co–NiWO4 NPs demonstrated outstanding efficiency, degrading a total of 95% of CR. The degradation kinetics were well-described by the Langmuir–Hinshelwood (L–H) kinetic model, indicating that photoabsorption played a crucial role in the rate-controlling step. These encouraging results suggest that Co–NiWO4 NPs hold promise as a viable option for addressing other pollutants in various applications.